If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -18 + -3n = -3(1 + 6n) -18 + -3n = (1 * -3 + 6n * -3) -18 + -3n = (-3 + -18n) Solving -18 + -3n = -3 + -18n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '18n' to each side of the equation. -18 + -3n + 18n = -3 + -18n + 18n Combine like terms: -3n + 18n = 15n -18 + 15n = -3 + -18n + 18n Combine like terms: -18n + 18n = 0 -18 + 15n = -3 + 0 -18 + 15n = -3 Add '18' to each side of the equation. -18 + 18 + 15n = -3 + 18 Combine like terms: -18 + 18 = 0 0 + 15n = -3 + 18 15n = -3 + 18 Combine like terms: -3 + 18 = 15 15n = 15 Divide each side by '15'. n = 1 Simplifying n = 1
| 2=6b-7b | | N-(-13)=2 | | -6(4n-4)=40-8n | | 5-7/46 | | 1200=0.03*b | | -4(r+4)=-30+3r | | 17.5=1.25*b | | -7n+14=-5(n-4) | | 3x+20+9(10x-12)+15x+17=10+9(3x+10x)+11+7x | | 148=4(8r+8)-3r | | 345/3= | | -4+4y+2=2 | | 4=5b-8+b | | 16/10=5/x | | 14.2/29= | | 1+5x-6=0 | | -96=-6(-4p-8) | | U=1/7gv | | 7t=80+9h | | X/3=14/2= | | 169=2x+2y | | (10)1/2 | | 4+5(3-6)+2= | | (10y)1/2 | | (5x/18)=(20/3) | | 78=.26x | | 6=2/5x | | 9(x-5)+7=9x+3 | | -3/10-2/5x=1/5 | | (5+x)(3+x)=48 | | -(8-2)+5x-6=-4 | | 10y^3-2y^2=0 |